ANALYSIS OF SOCIO-ECONOMIC IMPACTS OF THE COVID-19 PANDEMIC USING FACTOR ANALYSIS - Susilawati, Made; Sumarjaya, I Wayan; Srinadi, IGAM; Nilakusmawati, DPE; Suciptawati, NLP (PATTIMURA UNIVERSITY, 2023)
The purpose of this study is to identify the factors that influence the socio-economic impact of the Covid-19 pandemic. This study uses explanatory factor analysis that is an analysis that forms new random factors in which the later formed factors or constructs can be interpreted. The case study was conducted in Sawan Village, Sawan District, Buleleng Bali, with six variables explaining the economic impact, and 16 variables explaining the social impact. The results of the study show that there are three factors that explain the economic impact due to Covid-19. They are the income factor, the purchase of quotas and gadgets, and the expenditure factor with the total variance described being 82,178 percent. Meanwhile, the social impact due to the Covid-19 pandemic is explained by three factors, namely the fear of interacting in public places, the fear factor of doing activities outside the home, and the fear of using public facilities with a total variance that can be explained is 73,609 percent.